Employers expectations vis-à-vis graduates of faculties of economics: Results of a direct study - Tomasz Dorożyński; Janusz Świerkocki; Wojciech Urbaniak (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper presents employers' opinions concerning competencies they expect of graduates of Faculties of Economics with elements of environmental protection. In order to provide empirical input, we conducted a questionnaire-based study among 200 top managers of (mostly) businesses located in the Lodz region (voivodeship), including 194 enterprises and 6 entities do not involved in business but whose activities are, directly or indirectly, linked with environmental protection. The findings of our study demonstrate that while both soft and professional competencies acquired in the course of university studies are important to employers, the respondents valued soft competencies more. They found foreign languages to be the most important, although surprisingly they also attached high importance to a good command of Polish. When assessing university curricula, employers indicated that general courses, the foundations of a university education, remain important as a basis to improve the professional skills of university graduates and to reinforce their position in the labour market.
Keywords: 330; higher education; employers; graduates; economics and environmental protection